Penerapan Terapi Rendam Kaki Air Jahe Merah Hangat terhadap Tekanan Darah pada Lansia dengan Hipertensi di Wilayah Kerja Puskesmas Sukoharjo - Ulfa Nugraheni; Sitti Rahma Soleman (STIKES Columbia Asia Medan, 2024)
Background: The impact of hypertension that is not treated properly and uncontrolled will cause various complications, such as heart failure and coronary heart disease, in the brain there is a stroke, if it hits the kidneys there is chronic kidney failure, and if it hits the eyes there will be visual impairment. The various complications that may arise are very serious diseases and have an impact on the patient's psychology because of their low quality of life. Objective: To describe the results of blood pressure comparison before and after the application of Red Ginger Water Foot Soak Therapy in the elderly. Methods: This study used a descriptive research design with a case study approach by observing blood pressure in 2 elderly respondents, carried out 5 days for 1 consecutive week within 15 minutes. The instruments used are observation sheets, Blood Plesure Monitor, and stopwatch. Results: There is a decrease in blood pressure after giving Warm Red Ginger Water Foot Soak to Mrs. T from stage 2 hypertension to stage 1 hypertension and to Mr. S from stage 1 hypertension to stage 1 hypertension. S from stage 1 hypertension to prehypertension. Conclusion: The application of warm red ginger water foot soak therapy can potentially reduce blood pressure in the elderly with hypertension in both respondents.